A horizontal complaint in court enforcement proceedings – lights and shadows (Discourse of Law and Administration, 2022)
In court enforcement proceedings, a complaint is examined by the court which issued the decision under appeal, in a different composition. It is called horizontal complaint. This model of grievance weakens the control function. This makes it impossible for the court of second instance to perform the task of standardizing the jurisprudence. It is necessary to introduce statutory changes that will restore the previous model of a complaint examined by a court of second instance. A horizontal objection should be allowed only against some court decisions.
Keywords: court enforcement proceedings; complaints; appeals